Evaluation of Acute Toxicity of Ethanol Extract of Pirdot Leaf (Saurauia vulcani Korth.) in Rats - Simanjuntak, Nerly Juli Pranita; Rosidah; Yuandani (Talenta Publisher, 2020)
Traditionally pirdot leaves are used to treat various diseases. The purpose of this study was to determine determine the potential for acute toxicity of ethanolic extract of pirdot leaf (Saurauia vulcani Korth.) with value LD50 and hematological Parameters in rats. The acute toxicity of ethanolic extract of pirdot leaf was evaluated by OECD guidelines. The number of animals used in this research were 15 female rats. The control group was given Na CMC 0.5%, the treatment groups were given ethanolic extract of pirdot leaves with doses 2000 and 5000 mg/kg bw. The results showed that ethanolic extract of pirdot leaves with doses of 2000 and 5000 mg/kg bw did not show any toxicity signs. There was no mortality was observe. The ethanolic extract of pirdot leaves did not cause any changes in hematological parameters, these include red blood cells (RBC), hemoglobin, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet, white blood cells (WBC), neutrophils, lymphocytes, monocytes, eosinophils, and basophils levels as compared to normal control (P>0.05). It was estimated that LD50 of ethanolic extract of pirdot leaves was higher than 5000 mg/kg bw and the extract were practically non-toxic. The ethanolic extract of pirdot leaves did not cause any toxic effect on hematological parameters.